Нестационарное вдавливание затупленного жесткого тела в поверхность упругого слоя - Кубенко, В.Д. (Видавничий дім "Академперіодика" НАН України, 2007)
The nonstationary indentation for a blunted rigid body affecting the elastic layer is studied. The general problem formulation includes different boundary conditions on the free surface and contact region. A simplified nonmixed problem that is valid during early times and can serve as a rateable one for a later period is solved exactly.